Health and Zionism The Israeli Health Care System, 1948-1960 - Shvarts, Shifra (Rochester Studies in Medical History, 2008)
An exploration of the major conflicts and historic events that shaped the current Israeli health care system. In this follow-up to her 2002 book, The Workers' Health Fund in Eretz, Israel: Kupat Holim, 1911-1937, historian Shifra Shvarts investigates the political and social forces that influenced Israel's health care system and policy during the early years of state building. Among the struggles Shvarts explores in this penetrating study are the debate over immigration health policy and the Law of Return, enacted in 1950; the battles over universal healthcare between the Workers' Health Fund and the Israeli government led by prime minister Ben Gurion; the urgent organization of military medical services during wartime; and the contested establishment of renown civilian medical facilities. These early conflicts have had far-reaching implications that continue to be felt throughout Israeli society. While many European countries successfully established unified, state-run health care systems, Israel's political rivalries and social turbulence gave rise to a mélange of "sick funds," large and small, public and private, that influence and complicate the delivery of health care to this day. Health and Zionism: The Israeli HealthCare System, 1948-1960, sheds light on the major conflicts, leaders, and historic events that shaped the current Israeli health care system, and has relevance to developing health care systems worldwide. Shifra Shvarts is Associate Professor, Faculty of Health Sciences, Ben Gurion University, Israel, and is author of The Workers' Health Fund in Eretz Israel Kupat Holim, 1911-1937 (University of Rochester Press, 2002).